REFORMASI ADMINISTRASI DAN PENGETAHUAN PAJAK: PENGARUHNYA TERHADAP KEPATUHAN WPOP DI KPP PRATAMA SERANG BARAT - Kevin Adiyatma; Juliannes Cadith (LPPM STIA Banten, 2025)
This study focuses on analysing the influence of two factors (tax administration reform and the level of tax knowledge) on the compliance of Individual Taxpayers (WPOP) in carrying out their obligations on Income Tax (PPh) in the working area of KPP Pratama Serang Barat. This study adopts a quantitative approach, with the method of selecting respondents using purposive sampling technique. A total of 204 respondents were collected as a representative sample. Primary data was obtained through questionnaire distribution and analysed using multiple linear regression method. The results of the analysis show that both tax administration reform and tax knowledge have a significant influence on the level of WPOP compliance, both separately (partial) and together (simultaneous). Interestingly, tax knowledge has a greater contribution than administrative reform, indicating that adequate understanding of the tax system is more effective in shaping compliance behaviour than system changes alone. The regression equation obtained in this study: Y = -30.222 + 0.650X1 + 0.907X2, with a coefficient of determination (R²) of 52.5%, meaning that more than half of the variation in taxpayer compliance can be explained by the two variables. This finding strengthens the argument that the success of fiscal policy relies heavily on the integration between structural reforms in tax administration and the improvement of people's tax literacy capacity. Both are important foundations in encouraging voluntary and sustainable compliance.